Aspartate-β-hydroxylase induces epitope-specific T cell responses in hepatocellular carcinoma. Issue 10 (3rd March 2015) - Tomimaru, Yoshito; Mishra, Sasmita; Safran, Howard; Charpentier, Kevin P.; Martin, William; De Groot, Anne S.; Gregory, Stephen H.; Wands, Jack R.
Abstract Hepatocellular carcinoma (HCC) has a poor prognosis due to high recurrence rate. Aspartate-β-hydroxylase (ASPH) is a highly conserved transmembrane protein, which is over expressed in HCC and promotes a malignant phenotype. The capability of ASPH protein-derived HLA class I and II peptides to generate antigen specific CD4+ and CD8+ immune responses is unknown. Therefore, these studies aim to define the epitope specific components required for a peptide based candidate vaccine. Monocyte-derived dendritic cells (DCs) generated from the peripheral blood mononuclear cells (PBMCs) of HCC patients were loaded with ASPH protein. Helper CD4+ T cells and CD8+ cytotoxic T lymphocytes (CTLs) were co-incubated with the DCs; T cell activation was evaluated by flow cytometric analysis. Immunoinformatics tools were used to predict HLA class I- and class II-restricted ASPH sequences, and the corresponding peptides were synthesized. The immunogenicity of each peptide in cultures of human PBMCs was determined by IFN-γ ELISpot assay. ASPH protein-loaded DCs activated both CD4+ and CD8+ T cells contained within the PBMC population derived from HCC patients. Furthermore, the predicted HLA class I- and class II-restricted ASPH peptides were significantly immunogenic. Both HLA class I- and class II-restricted peptides derived from ASPH induce T cell activation in HCC. We observed that ASPH protein and related peptides were highly immunogenic in patients with HCC and produce the type of cellular immune responses required for generation of anti-tumor activity.